Collaboration Governance in Realizing Balbar as an Independent Village in Kota Tidore Kepulauan - Muksin, Isra; Djamal, Mansyur (Yayasan Ilomata, 2025)
Balbar Village in Tidore Islands City is trying to realize itself as an independent village through a collaborative governance approach. This study aims to analyze how collaboration between the government, the community, the private sector, and Civil Society Organizations (CSOs) can accelerate the achievement of village independence. This study uses a qualitative method with data collection through in-depth interviews, participatory observation, and documentation. The results of the study show that good governance collaboration can increase the efficiency of the independent village program, but there are several obstacles, such as low community participation and lack of financial literacy. To overcome these obstacles, it is necessary to improve communication between stakeholders and empower human resources (HR) in villages.